2022
DOI: 10.3389/fonc.2022.1032471
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland cancers in elderly patients: challenges and therapeutic strategies

Abstract: Salivary gland carcinomas (SGCs) are the most heterogeneous subgroup of head and neck malignant tumors, accounting for more than 20 subtypes. The median age of SGC diagnosis is expected to rise in the following decades, leading to crucial clinical challenges in geriatric oncology. Elderly patients, in comparison with patients aged below 65 years, are generally considered less amenable to receiving state-of-the-art curative treatments for localized disease, such as surgery and radiation/particle therapy. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 206 publications
0
5
0
Order By: Relevance
“…There are numerous both mono-and poly-chemotherapy that are used as a palliative treatment for patients with SGTs that do not benefit from local treatment modalities such as surgery or radiation [49]. However, Due to lack of congruent evidence-based data, the decision of using either adjuvant chemotherapy in the treatment of malignant SGTs or as a palliative agent must be on case by case so as to prevent possible related complications [50].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous both mono-and poly-chemotherapy that are used as a palliative treatment for patients with SGTs that do not benefit from local treatment modalities such as surgery or radiation [49]. However, Due to lack of congruent evidence-based data, the decision of using either adjuvant chemotherapy in the treatment of malignant SGTs or as a palliative agent must be on case by case so as to prevent possible related complications [50].…”
Section: Discussionmentioning
confidence: 99%
“…Curative treatment will be more effective and completely achievable in localized diseases. The epithelial tumors of major salivary glands and salivary-gland type tumors, also described in the paper by Colombo et al of this special issue(19), stated that good prognosis histotypes and early-stage diagnosis is less common in the elderly with respect to the younger patients. Furthermore, unspecified histotypes presented more frequently in the elderly.…”
mentioning
confidence: 84%
“…In 2020, 43% of SGCs occurred in the elderly, causing 12,339 cancer-specific deaths, with a male-to-female ratio of 1.3:1. In the next two decades, the new diagnoses in the elderly age group are expected to account for 80% of the total SGCs diagnoses ( 3 ). The review of the Surveillance, Epidemiology and End Results (SEER) Program database indicated that the incidence of major salivary glands and salivary gland-type cancers in patients over 65 years was 4 and 7 times higher, respectively, than that reported in younger patients and the overall 5-year survival rates were significantly better in young than in elderly subjects who, more frequently, presented histotypes with poor prognosis (e.g.…”
Section: Epidemiological Updatementioning
confidence: 99%
“…salivary duct cancer) or unspecified histotypes ( 3 ). Indeed, almost half of SGCs cases from the SEER dataset presented at diagnosis with localized disease, without significant differences between major salivary glands and salivary gland-type carcinomas, while elderly patients were diagnosed more frequently at a metastatic stage ( 3 ).…”
Section: Epidemiological Updatementioning
confidence: 99%
See 1 more Smart Citation